1997
DOI: 10.1002/(sici)1099-1298(199709)7:4<285::aid-casp407>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

‘You get the nicotine and that in your blood’—constructions of addiction and control in women's accounts of cigarette smoking

Abstract: In this study discourse analysis was used in order to gain a greater understanding of the multiple meanings that women smokers attach to cigarette smoking. The discursive constructions used by women to explain and justify their smoking behaviour were identified by analysing the transcripts of four semi-structured interviews. All respondents framed their accounts of cigarette smoking within a discourse of addiction, reflecting the prevalence of this construction within the disciplines of medicine, psychology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 9 publications
3
43
0
Order By: Relevance
“…Bortorff and colleagues 59 explicitly observed this in their interviews with adolescent smokers, and we also found this depersonalisation to be common across studies. One example is the limited use of personal pronouns in accounts of addiction, with references to smoking's effect on "the body", "the brain" or "the bloodstream" 59,62 55,59 .…”
Section: Ambivalence About Addiction To Smokingmentioning
confidence: 99%
See 2 more Smart Citations
“…Bortorff and colleagues 59 explicitly observed this in their interviews with adolescent smokers, and we also found this depersonalisation to be common across studies. One example is the limited use of personal pronouns in accounts of addiction, with references to smoking's effect on "the body", "the brain" or "the bloodstream" 59,62 55,59 .…”
Section: Ambivalence About Addiction To Smokingmentioning
confidence: 99%
“…For example, "it's like it's a drug" 62 , "we're just junkies, we need nicotine" 56 , "it's worse than heroin" 57 , or "smokers are preoccupied with where the next nicotine fix is, the nicotine monkey on their backs" 61 . Although, others denied this relationship, claiming they don't view their relationship to smoking like that of "a heroin addict" 55 Accounts of addiction that refer to nicotine in the "bloodstream" 57,62 , a "chemical dependency" 57,62 ; and "tolerance" 59 , reflect -with varying degrees of sophistication -a biomedical understanding of 'nicotine dependence'. Participants across studies often presented addiction as a "physical need", however we found that physical descriptions of addiction were rarely discussed in isolation from other factors such as family and peer influence.…”
Section: How Do Smokers Understand the Role Of Nicotine In Addiction mentioning
confidence: 99%
See 1 more Smart Citation
“…Gillies and Willig (1997) used discourse analysis to analyse women's accounts of smoking, and found the discourse of addiction could be divided into physiological and psychological accounts. The physiological discourse draws strongly on 'scientific' language ("you get the nicotine and that in your blood", "[nicotine] goes straight into the bloodstream and goes to the brain", p. 291).…”
Section: Addictionmentioning
confidence: 99%
“…This may be due to the focus on bio-behavioural factors within current addiction research rather than social ones (Gillies & Willig, 1997;Willms, 1991). West has recently argued for a return to the consideration of the role of self-labelling (e.g.…”
Section: Social Identity and Smokingmentioning
confidence: 99%